(untitled) (Universal International Scientific Journal, 2026)
This article conceptually analyzes the formation and development of the legal status of women in Uzbekistan within the framework of the intersection of Eastern and Western legal traditions. The main goal of the study is to identify the historical transformation of the status of women by revealing the interaction between national legal heritage, Islamic legal values, traditional social relations, and modern democratic legal principles.